Physical Characteristic Change Due To Difference of Age, Muscle Type, Cooking Time and Temperature Combination Native Chicken Meat - Djoko Winarso (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2009)
.